2018
DOI: 10.4081/aiol.2018.7266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of river discharge on zooplankton diet in the Godavari estuary (Bay of Bengal, Indian Ocean)

Abstract: In estuaries, detrital (i.e., non-living) organic matter (OM) contributes significantly to the particulate organic matter (POM) pool and we hypothesize that it may be a major source of estuarine zooplankton diet. To test this hypothesis, the isotopic composition of carbon (d13C) and nitrogen (d15N) of phytoplankton, zooplankton, and POM was assessed in the Godavari estuary (Bay of Bengal, Indian Ocean) during wet (November) and dry periods (January). As a result of higher riverine discharge, POM concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 82 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Among key issues unexplored in regional food-web investigations are the nutritional sources and grazing pathways that sustain zooplankton stocks during different seasons. Isotope measurements have suggested, for example, that zooplankton in river-influenced areas during the SWM might derive more food value from suspended detritus than phytoplankton (Mukherjee et al, 2018). High zooplankton biomass during the SIM has also been attributed to enhanced fluxes via the microbial loop (Madhupratap et al, 1996a;Jyothibabu et al, 2008b;Anjusha et al, 2013), but the magnitudes of grazing flows from heterotrophic bacteria and dominant picophytoplankton (e.g., Brown et al, 1999Brown et al, , 2002 have not been measured for any season.…”
Section: Zooplanktonmentioning
confidence: 99%
“…Among key issues unexplored in regional food-web investigations are the nutritional sources and grazing pathways that sustain zooplankton stocks during different seasons. Isotope measurements have suggested, for example, that zooplankton in river-influenced areas during the SWM might derive more food value from suspended detritus than phytoplankton (Mukherjee et al, 2018). High zooplankton biomass during the SIM has also been attributed to enhanced fluxes via the microbial loop (Madhupratap et al, 1996a;Jyothibabu et al, 2008b;Anjusha et al, 2013), but the magnitudes of grazing flows from heterotrophic bacteria and dominant picophytoplankton (e.g., Brown et al, 1999Brown et al, , 2002 have not been measured for any season.…”
Section: Zooplanktonmentioning
confidence: 99%
“…Zooplankton biomass in the mixed layer during SpIM in the Arabian Sea was found to be on par with the biomass during the more (primary) productive monsoons because of the microbial loop (Madhupratap et al, 1996). Mukherjee et al (2018) in a study off the coast of the Bay of Bengal found that detrital organic matter is a major source of zooplankton diet.…”
Section: Introductionmentioning
confidence: 99%